Experimental study of heat transfer enhancement with segmented flow in a microchannel by using molecule-based temperature sensors. (April 2017) - Huang, Chih-Yung; Huang, Bo-Han; Cheng, Fon-Ru; Chen, Shao-Wen; Liou, Tong-Miin
Highlights: A novel experimental technique of molecule-based temperature sensors was applied. Detailed fluid/wall temperature distributions in the microchannel were obtained. Up to 30% heat transfer improvement was identified in segmented microchannel flow. Micro-PIV measurements were applied to obtain the velocity and vorticity profiles. Abstract: This paper presents an experimental study of heat transfer enhancement with liquid-gas two-phase segmented microchannel flows by utilizing a novel technique of molecule-based temperature sensors. A serpentine microchannel was constructed and steady liquid and gas segments of ethanol and air were successfully produced at various flow rates. A molecule-based temperature sensor made of Tris(2, 2′-bipyridyl) ruthenium was utilized in the liquid segments by dissolving in ethanol as temperature-sensitive fluid and mixing in a dope to produce temperature-sensitive paint in order to retrieve fluid and surface temperature data, respectively. Three cases of different liquid and gas flow rates were tested. The heat transfer enhancements of these three cases were carefully examined under constant heat flux thermal boundary conditions, and the increased heat transfer was evaluated in comparison with the single-phase flow, where only liquid was injected in the microchannel. An improvement of up to 30% in the averaged Nu number of the microchannel flow was determined for Case 3, with a high gas flow rate and short liquid segments. Velocity and vorticity profiles in the liquid segments at different gas and liquid flow rates were also studied using a micro-particle image velocimetry technique. Stronger circulation was observed in Case 3, which confirmed the results from the heat transfer analysis, namely that more efficient heat transfer occurs with strong circulation in short liquid segments when a high gas flow rate is applied. The results of the present study provide detailed temperature profiles in segmented flow as well as the evolution of the Nu number from the entrance to the exit of a serpentine microchannel.